Effect of Mindfulness Meditation on Reducing Stress in College Students in Indonesia - Agustina, Maria (International Journal of Psychology, 2024)
Purpose: The aim of the study was to analyze the effect of mindfulness meditation on reducing stress in college students. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Mindfulness meditation significantly reduces stress among college students by enhancing emotional regulation, promoting relaxation, and improving coping mechanisms. Studies show that students practicing mindfulness experience lower levels of anxiety, better academic focus, and improved overall well-being compared to those who do not. Regular meditation fosters greater resilience to stress by encouraging present-moment awareness and reducing overthinking. Additionally, integrating mindfulness programs into college settings can create supportive environments that enhance mental health. Unique Contribution to Theory, Practice and Policy: Mindfulness-based stress reduction (MBSR) framework, cognitive appraisal theory & self-determination theory (SDT) may be used to anchor future studies on the effect of mindfulness meditation on reducing stress in college students. Colleges should integrate mindfulness training into orientation programs to help first-year students navigate the academic, social, and emotional transitions of college life. Policymakers should mandate the inclusion of evidence-based well-being programs, including mindfulness meditation, as part of a holistic approach to mental health in higher education.